How do we see those who fall? The influence of causal attribution and gender on the perceptions of employee competence and future promotability after status loss - Simões, Lorena Cardoso (2020)
We investigate how causal attributions and gender can affect perceptions about employee competence and promotability after status loss. We theorize that the underlying reason (dispositional vs. situational) for the failure event, which resulted in the status loss, will have a substantive impact on peers' judgments after the downfall. In an online experiment (Study 1), we found no significant differences in perceptions of employees who lost status due to internal causes (i.e., dispositional) versus external reasons (i.e., situational). However, a post hoc analysis indicated that the employee gender is moderately significant in determining confidence in promotion, but not in the perception of competence when using the control variables. In a second online experiment (Study 2), we recreate the vignette removing the attribution inferences and introducing the employee's previous status as a variable of interest. Contrary to our expectations and the literature, neither employee gender nor initial status significantly impacted how employees were perceived after a status-loss event. We discuss the implications of this research for status-loss literature and suggest avenues for future analysis.